Qualidade da Atenção à Saúde do Homem na Atenção Primária à Saúde no Brasil: um estudo a partir do Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica - Wanicy Pascoal Espindola (2019)
In Brazil, some initiatives were developed by the Ministry of Health focused on the quality of Primary Health Care (PHC), among them the National Program for Improving Access and Quality of Primary Care (PMAQ-AB), a strategy changes in the conditions and way of operation of the Basic Health Units, proposing qualification of care processes and application of financial incentive. Developing actions directed to men's health has still been a challenge for the public health system in the country, so it becomes necessary to evaluate the primary level services provided to the male public, in order to favor the inclusion of this population in health services and contribute to the reduction of morbidity and mortality indicators. In this sense, an instrument that has been used for indirect assessment of the first level of health care refers to Ambulatory Care Sensitive Conditions (ACSC), considered an important indicator of access and effectiveness of PHC. This study aims to relate the quality of PHC in Brazilian municipalities that participated in the second cycle of PMAQ-AB with ACSCs in the male population aged 20 to 59 years from 2012 to 2016. This is a time series ecological study, quantitative approach, with secondary data from the PMAQ-AB and the Hospital Information of the Unified Health System. We included municipalities with 80% or more adherence of their teams to PMAQ-AB, totaling 3.897 municipalities. The municipalities were stratified into two groups, categorized as low and medium/high quality of PHC, based on the average of the PMAQ-AB scores obtained by the health teams of each municipality. The Generalized Equations Estimating (GEE) model was used through a Log-Linear Gamma marginal regression. For the selection of control variables in the multivariate analysis, the forward and backward methods were employed. It was considered statistically significant valor-p< 0.05. The results showed an average increase in ACSCS rates of 38% for municipalities with a population of 20.001 to 50.000 inhabitants compared to the metropolises and 14% for every 1 bed per 1000 inhabitants. Regarding health plans, there was an inverse association in which the 10% increase in plan coverage decreases 4% of ACSC rates. The low-quality municipalities of PHC presented an average fall of 5% per year [IC: 4%; 6%] in the ICSAP rate and medium/high quality municipalities dropped by an average of 4% per year [IC: 3%; 5%]. Due to the overlap of confidence intervals, it was not possible to state that there was a difference in the trend of reducing the ACSC rate for both groups of municipalities. It was observed that several factors were related both in the punctual assessment of PHC, based on data from PMAQ-AB, and the lack of control of all confounding variables in ACSCS rates. However, it is noteworthy that improvements in PHC may have favored the reduction of sensitive hospitalizations, which reinforces the importance of financial investments and directing public policies.